EFISIENSI RUMAH SAKIT JIWA PEMERINTAH DI PROVINSI JAWA TENGAH DAN DIY SEBELUM DAN SESUDAH JKN DENGAN MENGGUNAKAN TWO-STAGE DATA ENVELOPMENT ANALYSIS (DEA) - Rina Indrayanti; Lutfan Lazuardi; Mubasysyir Hasanbasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: During a national health insuranceimplementation, efficiency improvement becomes an importantissue as a result of the change of a payment method from freefor service to fixed pricing mechanism of INA CBG's bycontaining cost and improving quality. Inefficiency occurs whena psychiatric hospital uses an excessive input resource toproduce a given level output.Objective: This study aimed to measure the level of efficiencyof government psychiatric hospitals in the provinces of CentralJava and Yogyakarta before and after the implementation ofJKN. Methods: A descriptive quantitative study was conductedusing two-stage data envelopment analysis (DEA). The firststage was to measure hospital efficiency. Second stage usedpaired samples t-test to analyze different mean of BOR, LOS,BTO, TOI and cost efficiency score. This study used secondarydata from financial report, human resources report, hospitalpatient visit report of 5 psychiatric hospitals in central java andDIY province, period 2010 until 2014.Results: Efficiency measurement using DEA CRS inputorientedmodel obtained the mean of cost efficiency score was0,896. Mean of efficiency score decreased during a transitionperiod of national health insurance implementation from 0,947in 2013 became 0,866 in 2014. Soedjarwadi hospital was theonly one of a psychiatric hospital that achieved cost efficiency in2014. Paired samples t test analysis showed that there was nodifference of mean of BOR, LOS, BTO, TOI and score costefficiency before and after efficiency improvement in 2013 from2010. There was no difference of mean of BOR, LOS, BTO andscore efficiency before and after implementation of nationalhealth insurance. The only one variable had difference of meanbefore and after implementation of national health insurancewas TOI.Conclusion: Most psychiatric hospital in this study are stillinefficient. National health insurance has not been able toimprove efficiency in the early implementation period.Decreasing of efficiency score happened because of thedecreasing of hospital output.